(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
According to behavior analysis, feelings and emotions should be approached with the concepts and principles empirically validated in the study of behavioral phenomena. One of these references is the causal mode of selection by consequences. However, the compatibility of this causal mode with respondent behavioral phenomena, with regard to which it is said that the response is a function of an antecedent (eliciting) stimulus, requires clarification. The present paper examines some possible relations among respondent and operant responses in the case of emotions, and the possibility of explaining emotional phenomena based on the causal mode of selection by consequences. It is pointed that emotional responses may be conditioned to the presence of a stimulus which antecedes an operant response, after the emotional response has been elicited by the stimulus which is consequent to the emission of that operant response. With regard to such relations, the causal mode of selection by consequences would be explanatory of both operant and respondent components of emotions.